Startup Acquisitions, Error Costs, and Antitrust Policy - Bryan, Kevin A.; Hovenkamp, Erik (The University of Chicago law review, 2020)
Startup acquisitions by dominant incumbents, especially in high tech, have recently attracted significant attention. Many researchers and practitioners worry about harms to competition or innovation. However, there has been very little antitrust enforcement in this area. This is emblematic of a prominent feature of modern antitrust law: a strong preference for erring on the side of nonenforcement. A leading rationale for this preference is the claim that market power self-corrects by attracting new entrants who discipline incumbents. As a result, plaintiffs generally face very demanding evidentiary requirements, which are particularly hard to satisfy in the case of startup acquisitions. A typical startup is both new and small, providing little data for estimating competitive effects. Despite this uncertainty, it is unlikely that society is best served by a policy of near-universal inaction. Recent work in economics, both empirical and theoretical, identifies various harms to competition and innovation as a result of startup acquisitions in concentrated markets. Further, the traditional error cost argument is particularly inapposite in this context, as startup acquisitions may be undertaken precisely because they forestall competitive entry. We therefore argue for expanded antitrust intervention (that is, more than zero) in startup acquisitions by dominant incumbents. In practice, the acquirer's market power and the transaction value may be useful signals of the risk of harm.